CLINICAL AND LABORATORY CHARACTERISTICS OF HERPETIC INFECTIONS (Лучшие интеллектуальные исследования, 2025)
Abstract: in recent years, there has been a steady increase in recurrent forms of infection caused by herpes simplex viruses of type 1 and type 2 of various localization. Numerous studies have shown that 65-90% of the adult and child population of the planet are infected with herpes simplex viruses, and from 9 to 25% of them suffer from recurrent forms of diseases, in 30% the infection is detected in a subclinical and latent form. HSV antigen was found in 36% of children with frequent respiratory diseases. It is proved that patients with chronic herpetic infections develop oncological and autoimmune diseases, infertility, fetal pathology much more often. Herpes viruses induce the processes of atherosclerosis, affect the process of mental development of a person, cause pathology of nerve cells. Severe course of herpes infection can be a marker of HIV infection. This article will provide information about many common herpes infections among children in recent years, showing their characteristics in a clinical laboratory. Keywords: herpetic infection, laboratory, children's age.